The role of prevention of dental diseases in the system of providing dental care - Popovych, З. Б.; Rozhko, М. М.; Melychuk, М. В.; Kukurudz, Н. І. (Actual Dentistry, 2023)
Resume. Dental morbidity in the population of Ukraine is characterized by high prevalence and intensity. number of factors contribute to this: ecological living conditions, stress factors, general health and the state of hygienic care of the oral cavity The aim of this work is to review and systematize literature data devoted to the study of the influence of various factors on the state of children's dental health. A combination of many factors contributes to the high level of dental morbidity: unfavorable environmental living conditions, psycho-emotional state of children. This is especially relevant in the current difficult time for Ukraine, when the country is at war. Social factors also have a significant impact on the state of dental morbidity in children. A significant role in the occurrence and course of dental pathology is played by the general state of health, the presence of somatic pathology, as well as the state of oral hygiene. One of the important tasks is the formation of risk gr ups of children, followed by followup and a complex of medical and preventive measures. Conclusion. It has been proven that the features and level of dental morbidity are largely determined by a complex of unfavorable factors. However, compliance with even simple manipulations, in particular hygienic care of the oral cavity, can contribute to the stabilization and improvement of dental health.